Lichens as Bio-Indicator for Air Pollution and Their Relevancy in Pokhara, Nepal - Panta, Kalyan (Himalayan Biodiversity, 2020)
The use of naturally occuring lichens as a bioindicator to assess the health of environment is a well proved potential strategy to monitor any habitat without device/ instruments. The article clearly revealed that the quality of air pollution has been a major problems in city area and suburban areas. In this case, the lichens could be used as reliable indicators to trace the air polluted sites and It could be useful to combat the decreasing anthropogenic disturbances such as vehicular emission, constrution of civil works, etc. The essence of these studies provide an understanding of environmental impacts and can follow the policy makers to protect the Lichen flora and air pollution related problems.